A Bayesian network meta-analysis of 5 different fusion surgical procedures for the treatment of lumbar spondylolisthesis. Issue 14 (April 2020) - Tang, Linjun; Wu, Yong; Jing, Daping; Xu, Yong; Wang, Cheng; Pan, Jingjing
Abstract : Abstract: Lumbar fusion has been widely used to treat lumbar spondylolisthesis, which can be classified into 5 types according to its approach, including posterolateral fusion (PLF), posterior lumbar interbody fusion (PLIF), transforaminal lumbar interbody fusion (TLIF), posterolateral fusion plus anterior lumbar interbody fusion (PLFplusALIF), and posterolateral fusion plus posterior lumbar interbody fusion (PLFplusPLIF). Theoretically, each approach has its own advantages and disadvantages, however, no studies are available to compare them. A network meta-analysis (NMA) was performed in this study and the results were illustrated by the mean difference (MD) or odds ratio (OR). Meanwhile, the preferable treatments were indicated using the surface under the cumulative ranking curve (SUCRA). All data were analyzed and graphs were plotted using R 3.4.1. A total of 28 literatures were included in this meta-analysis. PLIF was the most effective treatment for pain relief. Conversely, TLIF was the most effective method for reducing vertebral slippage. For patients with isthmic spondylolisthesis (IS), PLIF performed the best in terms of Visual Analogue Scale (VAS) score, Oswestry Disability Index (ODI) score, fusion rate, blood loss, and complication rate. For patients with degenerative spondylolisthesis (DS), TLIF was the best from the points of view of VAS, complication rate, and vertebral slippage reduction. PLIF and TLIF are identified as the optimal treatments for all lumbar spondylolisthesis cases, among which, PLIF may be the preferred choice for pain relief, while TLIF can offer the best outcomes in terms of vertebral slippage reduction. Furthermore, TLIF has displayed the best clinical outcomes and tolerability for DS patients. Abstract : Supplemental Digital Content is available in the text